The Relationship of Social Interaction With the Loneliness of the Elderly - Jajuk Kusumawaty; Devina Sutandi; Asep Gunawan; Dedi Supriadi (LPPM STIKes Muhammadiyah Ciamis, 2023)
Purpose: to determine the relationship between social interaction and the loneliness of the elderly in Ciamis Village. Methods: the method in this study is quantitative, with a cross sectional approach, data collection using a questionnaire distributed through a questionnaire. Sample: The sample in this study amounted to 96 respondents. This research was conducted in March–April 2022. Result: Based on the results of the study, of the 96 respondents, there were 22 (40%) in the category of good social interaction with loneliness and 32 (59.3%) in the category of good social interaction with loneliness. Not lonely: 9 respondents (30%) in the category of social interaction are sufficient with loneliness; 12 respondents (100%) in the category of social interaction are less with not loneliness. From the result of the Chi-Square Statistical Test, the value (0.023) <value (0.05). Conclusion: Good social interaction will reduce loneliness in the elderly.